Secondary battery and method for manufacturing the same

CN115552685BActive Publication Date: 2026-10-30SAMSUNG ELECTRONICS CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180032847.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-10
Filing Date
2021-04-21
Publication Date
2026-10-30
Estimated Expiration
2041-04-21

AI Technical Summary

Benefits of technology

[0029]根据实施方式,二次电池可防止由在充电过程期间在负极侧处析出的锂(锂金属)导致的短路。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115552685B_ABST
    Figure CN115552685B_ABST
Patent Text Reader

Abstract

A secondary battery includes a positive electrode layer including a positive electrode active material layer; a negative electrode layer including a negative electrode current collector and a metal layer disposed on the negative electrode current collector; a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer; and a graphite interlayer disposed between the solid electrolyte layer and the negative electrode layer, wherein the interlayer includes a graphite material having a crystallite size of about 1000 angstroms to about 1500 angstroms when measured by a (110) diffraction peak, and having a hexagonal interlayer spacing in a c-axis direction of about 500 angstroms to about 800 angstroms when measured by a (002) diffraction peak, the graphite material having an aspect ratio in a range of about 0.44 to about 0.55.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to secondary batteries and methods for preparing said secondary batteries. Background Technology

[0002] Recently, all-solid-state secondary batteries using solid electrolytes have attracted attention. It has been suggested to use lithium as the negative electrode active material to improve the energy density of all-solid-state secondary batteries. For example, the specific capacity (capacity per unit weight) of lithium is known to be about 10 times that of graphite, which is commonly used as the negative electrode active material. Therefore, when lithium is used as the negative electrode active material, all-solid-state secondary batteries can be fabricated as thin films, and the battery output can be improved. However, there is still a need for improved battery materials. Summary of the Invention

[0003] Technical issues

[0004] It provides a secondary battery with excellent performance that prevents short circuits that can occur due to lithium (lithium metal) precipitated (deposited) in the negative electrode layer during the charging process of an all-solid-state secondary battery.

[0005] We provide secondary batteries with excellent charge / discharge characteristics.

[0006] We offer rechargeable batteries that are easier to manufacture and have lower manufacturing costs compared to commercially available rechargeable batteries.

[0007] Solution to the problem

[0008] Other aspects will be set forth in part in the following description and will also be apparent from the description itself.

[0009] According to one aspect, a secondary battery includes: a positive electrode layer comprising a positive electrode active material layer; a negative electrode layer comprising a negative electrode current collector and a metal layer disposed on the negative electrode current collector; a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer; and a graphite interlayer disposed between the solid electrolyte layer and the negative electrode layer, wherein the graphite interlayer comprises a graphite material having a crystallite size of about 1000 Å to about 1500 Å as measured by the (110) diffraction peak when analyzed by X-ray diffraction, and having a hexagonal interplanar spacing of about 500 Å to about 800 Å in the c-axis direction as measured by the (002) diffraction peak when analyzed by X-ray diffraction, the aspect ratio of the graphite material being in the range of about 0.44 to about 0.55.

[0010] The metal layer may include at least one of lithium or a lithium alloy.

[0011] The lithium alloy may include at least one of the following: Li-Al alloy, Li-Sn alloy, Li-In alloy, Li-Ag alloy, Li-Au alloy, Li-Zn alloy, Li-Ge alloy, or Li-Si alloy.

[0012] The positive electrode active material layer may include at least one of the following: lithium cobalt oxide (LCO), lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide (NCA), lithium nickel cobalt manganese oxide (NCM), lithium manganate, or lithium iron phosphate.

[0013] The solid electrolyte layer may include at least one of the following: Li 3+x La3M2O 12 , where 0≤x≤10; Li3PO4; Li x Ti y (PO4)3, where 0<x<2 and 0<y<3; Li x Al y Ti z (PO4)3, where 0<x<2, 0<y<1, and 0<z<3; Li 1+x+y (Al a Ga 1-a ) x (Ti b Ge 1-b ) 2-x Si y P 3-y O 12 , where 0≤x≤1, 0≤y≤1, 0≤a≤1, 0≤b≤1; Li x La y TiO3, where 0<x<2 and 0<y<3; Li x M y P z S w , where M is at least one of Ge, Si, or Sn, and 0<x<4, 0<y<1, 0<z<1, and 0<w<5; Li x N y , where 0<x<4 and 0<y<2; Li x PO y N z , where 0<x<4, 0<y<5, and 0<z<4; Li x Si y S z , where 0<x<3, 0<y<2, and 0<z<4; Li x P y S z, where 0<x<3, 0<y<3, and 0<z<7; Li₂O; LiF; LiOH; Li₂CO₃; LiAlO₂; Li₂O-Al₂O₃-SiO₂-P₂O₅-TiO₂-GeO₂; or Li x La y M z O 12 , wherein M is at least one of Te, Nb, or Zr, and 1<x<5, 0<y<4, and 0<z<4.

[0014] The thickness of the solid electrolyte layer may be in the range of about 10 μm to about 250 μm.

[0015] The graphite intermediate layer may include a binder.

[0016] The binder may include at least one of the following: polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polyvinyl alcohol-polyacrylic acid (PVA-PAA) copolymer, carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and based on the total weight of the graphite intermediate layer, the amount of the binder may be in the range of about 1 weight percent (wt%) to about 10 wt%.

[0017] The graphite intermediate layer may further include at least one of the following: iron (Fe), zirconium (Zr), gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), or zinc (Zn).

[0018] The secondary battery may be a lithium battery.

[0019] The positive electrode layer may further include a positive current collector disposed on the surface of the positive active material layer.

[0020] According to another aspect, the method for preparing the secondary battery may comprise: providing a solid electrolyte layer; mechanically grinding a surface of the solid electrolyte layer to provide a ground surface; bringing the solid electrolyte layer into contact with an oxidizing gas to provide an oxidized solid electrolyte layer; drying the solid electrolyte layer in air to provide a dried solid electrolyte layer; coating a graphite intermediate layer on the ground surface to provide a coated solid electrolyte layer; disposing a stack comprising a metal layer and a negative electrode current collector on the coated solid electrolyte layer to provide a negative electrode layer; and disposing a positive electrode layer comprising a positive electrode active material layer on a surface of the solid electrolyte layer opposite to the negative electrode layer, wherein the graphite intermediate layer comprises a graphite material that has a crystallite size of about 1000 angstroms to about 1500 angstroms measured by the (110) diffraction peak when analyzed using X-ray diffraction, and has a hexagonal crystal plane spacing in the c-axis direction of about 500 angstroms to about 800 angstroms measured by the (002) diffraction peak when analyzed by X-ray diffraction, and the aspect ratio of the graphite material in the graphite intermediate layer is in the range of about 0.44 to about 0.55.

[0021] The coating of the graphite intermediate layer may be provided by ink coating or pencil-drawing.

[0022] The disposing of the stack comprising the metal layer and the negative electrode current collector further comprises cold isostatic pressing to dispose the stack comprising the metal layer and the negative electrode current collector on the graphite intermediate layer.

[0023] The positive electrode active material layer may comprise at least one of the following: lithium cobalt oxide (LCO), lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide (NCA), lithium nickel cobalt manganese oxide (NCM), lithium manganate, or lithium iron phosphate.

[0024] The solid electrolyte layer may comprise a solid electrolyte material, and the solid electrolyte material is at least one of the following: Li 3+x La3M2O 12 , wherein 0≤x≤10; Li3PO4; Li x Ti y (PO4)3, wherein 0<x<2 and 0<y<3; Li x Al y Ti z (PO4)3, wherein 0<x<2, 0<y<1, and 0<z<3; Li 1+x+y (Al a Ga 1-a ) x (Ti b Ge 1-b ) 2-x Si y P3-y O 12 , where 0≤x≤1, 0≤y≤1, 0≤a≤1, and 0≤b≤1; Li x La y TiO3, where 0<x<2 and 0<y<3; Li x M y P z S w , where M is at least one of Ge, Si, or Sn, and 0<x<4, 0<y<1, 0<z<1, and 0<w<5; Li x N y , where 0<x<4 and 0<y<2; Li x PO y N z , where 0<x<4, 0<y<5, and 0<z<4; Li x Si y S z , where 0<x<3, 0<y<2, and 0<z<4; Li x P y S z , where 0<x<3, 0<y<3, and 0<z<7; Li2O; LiF; LiOH; Li2CO3; LiAlO2; Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2; and Li x La y M z O 12 , where M is at least one of Te, Nb, or Zr, and 1<x<5, 0<y<4, and 0<z<4.

[0025] The metal layer may include at least one of lithium or a lithium alloy.

[0026] The positive electrode layer may further include a positive electrode current collector disposed on a surface of the positive electrode active material layer.

[0027] The graphite intermediate layer may further include at least one of the following: iron (Fe), zirconium (Zr), gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), or zinc (Zn).

[0028] Beneficial Effects of the Invention

[0029] According to the embodiment, the secondary battery can prevent short circuits caused by lithium (lithium metal) precipitated at the negative electrode side during charging.

[0030] The secondary battery according to the embodiment may have excellent charge / discharge characteristics.

[0031] The secondary battery according to the embodiment may have beneficial characteristics such as ease of processing and reduced manufacturing costs. Attached Figure Description

[0032] The above and other aspects, features, and advantages of some embodiments of this disclosure will become more apparent from the following description taken in conjunction with the accompanying drawings, wherein:

[0033] Figure 1 A cross-sectional schematic diagram showing the structure of the secondary battery according to an embodiment;

[0034] Figure 2 A scanning electron microscope (SEM) image of a cross-section of a secondary battery after it has been overcharged according to an embodiment.

[0035] Figure 3A This is a cross-sectional schematic diagram showing the structure of the battery before it can be recharged into a commercially available rechargeable battery;

[0036] Figure 3B This is a schematic diagram showing a cross-section of a commercially available secondary battery after it has been overcharged.

[0037] Figure 3C SEM image of a cross-section of a commercially available secondary battery after it has been overcharged;

[0038] Figure 4 A graph showing the count (in arbitrary units) of graphite-based material included in a graphite-based intermediate layer versus the diffraction angle (°2θ) as analyzed by X-ray diffraction using Cu Kα radiation.

[0039] Figure 5A SEM image of the graphite-based intermediate layer according to the embodiment;

[0040] Figure 5B To show when analyzed by X-ray diffraction, Figure 5A A graph showing the element analysis of the first selected region in the graph;

[0041] Figure 5C To show when analyzed by X-ray diffraction, Figure 5A A graph of element analysis of the second selected region in the diagram;

[0042] Figure 5D To show when analyzed by X-ray diffraction, Figure 5A A graph of element analysis in the third selection region;

[0043] Figure 6A-6G A schematic diagram illustrating the secondary battery during each step of the preparation of the secondary battery according to the embodiment;

[0044] Figure 7 A graph showing energy efficiency (%) versus charge / discharge cycle number (#) illustrates the output characteristics of the secondary battery according to the embodiment and the secondary battery prepared in Comparative Example 1; and

[0045] Figure 8 Voltage (V) versus area capacity (mAh / cm²) 2 The figure shows the charging / discharging characteristics of the secondary battery according to the embodiment. Detailed Implementation

[0046] The embodiments will now be described in detail, examples of which are shown in the accompanying drawings, wherein the same reference numerals always refer to the same elements. In this respect, the embodiments may take different forms and should not be construed as limited to the description set forth herein. Therefore, the embodiments are described below only by reference to the accompanying drawings to illustrate aspects. As used herein, the term "and / or" includes any and all combinations of one or more of the associated enumerated items. Expressions such as "at least one of" modify the entire list of elements without modifying any individual element of the list when appearing before or after the list of elements.

[0047] In the following description, since the inventive concept is open to many variations and numerous embodiments, specific embodiments will be illustrated in the accompanying drawings and described in detail in the written description. However, this is not intended to limit the inventive concept to specific practices, and it will be understood that all variations, equivalents, and substitutions without departing from the spirit and scope of the invention are covered by the inventive concept.

[0048] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the inventive concept. Singular expressions cover plural expressions unless they have a distinct meaning in the context. As used herein, it will be understood that terms such as “comprising,” “having,” and “including” are intended to indicate the presence of the features, quantities, steps, actions, components, parts, ingredients, materials, or combinations thereof disclosed in this specification, and are not intended to exclude the possibility that one or more additional features, quantities, steps, actions, components, parts, ingredients, materials, or combinations thereof may be present or added. The symbol “ / ” used herein may be interpreted as “and” or “or” depending on the context.

[0049] Throughout this specification, it will be understood that when a component, such as a layer, film, region, or plate, is referred to as being "on" another component, the component may be directly on said other component or an intermediate component may be present thereon. Conversely, when an element is referred to as being "directly on" another element, no intermediate element is present. Throughout this specification, although terms such as "first," "second," etc., may be used to describe various components (components), regions, layers, or parts, such terms are not limited to these terms. The above terms are used only to distinguish one component (component), region, layer, or part from another. Therefore, without departing from the teachings herein, the terms "first element," "component," "region," "layer," or "part" discussed below may refer to a second element, component (component), region, layer, or part.

[0050] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting. For example, “element” has the same meaning as “at least one element” unless the context clearly indicates otherwise. “At least one” should not be construed as limiting “a, an”. “Or” means “and / or”. It will be further understood that the terms “comprising” or “including” as used in this specification indicate the presence of the stated features, areas, integrals, steps, operations, elements, and / or component portions, but do not exclude the presence or addition of one or more additional features, areas, integrals, steps, operations, elements, component portions, and / or collections thereof.

[0051] Furthermore, relative terms such as “lower” or “bottom” and “upper” or “top” may be used herein to describe the relationship between one element and another element as shown in the figures. It will be understood that, in addition to the orientations depicted in the figures, relative terms are also intended to cover different orientations of the device. For example, if the device in one of the figures is flipped, the element described as being on the “lower” side of another element will be oriented on the “upper” side of said other element. Thus, depending on the specific orientation of the figure, the exemplary term “lower” can cover both “lower” and “upper” orientations. Similarly, if the device in one of the figures is flipped, the element described as being “below” or “under” another element will be oriented “above” said other element. Thus, the exemplary terms “below” or “under” can cover both “above” and “below” orientations.

[0052] As used herein, “about” or “approximately” includes the stated value and means within an acceptable range of deviations from the specific value, as determined by a person skilled in the art taking into account the measurement in question and the errors associated with the measurement of the specific quantity (i.e., limitations of the measurement system). For example, “about” may mean within one or more standard deviations relative to the stated value, or within ±30%, 20%, 10%, or 5%.

[0053] Unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure pertains. It will be further understood that terms, such as those defined in common dictionaries, should be interpreted as having the same meaning as they have in the context of this disclosure and the relevant field, and will not be interpreted in an idealized or overly formal sense unless clearly defined herein.

[0054] Exemplary embodiments are described herein with reference to cross-sectional views that serve as schematic representations of idealized embodiments. Thus, deviations from the shapes shown in the figures will be anticipated as a result of, for example, manufacturing techniques and / or tolerances. Therefore, the embodiments described herein should not be construed as limited to the specific shapes of the regions illustrated herein, but rather include deviations in shape caused, for example, by manufacturing processes. For example, regions illustrated or described as flat may typically have rough and / or non-linear characteristics. Furthermore, sharp corners in the figures may be rounded. Therefore, the regions illustrated in the figures are schematic in nature, and their shapes are not intended to illustrate the precise shapes of the regions nor to limit the scope of the claims.

[0055] Examples of methods using lithium as the negative electrode active material may include methods using lithium or lithium alloys as the negative electrode active material layer and methods in which the negative electrode active material layer is not formed on the negative electrode current collector. In the method in which the negative electrode active material layer is not formed on the negative electrode current collector, a solid electrolyte layer is formed on the negative electrode current collector, and lithium is deposited at the interface between the negative electrode current collector and the solid electrolyte by charging the battery and can be used as an active material. The negative electrode current collector is formed of a metal that does not form alloys or compounds with lithium. However, in these methods in which lithium is used as the active material, lithium tends to form columnar structures, which generate regions with low density within the negative electrode layer. This results in regions of high local density, which can lead to low energy efficiency and / or short circuits in all-solid-state secondary batteries, and therefore requires improved negative electrode layers in all-solid-state secondary batteries.

[0056] Hereinafter, a secondary battery and its preparation method will be described in detail with reference to the accompanying drawings, according to one or more embodiments. In the drawings, the width and thickness of enlarged layers and regions are shown for clarity and ease of explanation. The same reference numerals in the drawings denote the same elements.

[0057] Figure 1 This is a cross-sectional schematic diagram showing the structure of a secondary battery according to an embodiment. Figure 2 This is a scanning electron microscope (SEM) image of a cross-section of a secondary battery after it has been overcharged according to an embodiment. Figure 3A This is a cross-sectional schematic diagram showing the structure of a commercially available rechargeable battery before it is charged. Figure 3B This is a schematic diagram of the cross-section of a commercially available secondary battery after it has been overcharged. Figure 3C This is an SEM image of a cross-section of a commercially available secondary battery after it has been overcharged. Figure 4 This is a diagram of the graphite-based material included in the graphite-based intermediate layer, analyzed by X-ray diffraction using Cu Kα radiation according to an embodiment. Figure 5A SEM image of a graphite-based intermediate layer according to an embodiment. Figure 5B To display Figure 5A The figure shows the elemental analysis of the first selected region using X-ray diffraction analysis with Cu Kα radiation. Figure 5C To illustrate when X-ray diffraction analysis is performed using Cu Kα radiation Figure 5A A graph showing the element analysis of the second selected region. Figure 5D To illustrate when X-ray diffraction analysis is performed using Cu Kα radiation Figure 5A A graph showing the element analysis of the third selection region in the diagram.

[0058] Reference Figure 1 and 2 The secondary battery 1 according to the embodiment may include a positive electrode layer 10; a negative electrode layer 20; a graphite interlayer 30; and a solid electrolyte layer 40. In the embodiment, the positive electrode layer 10 may include a positive electrode current collector 11 and a positive electrode active material layer 12. For example, the positive electrode current collector 11 may include at least one of the following: indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or alloys thereof. For example, the positive electrode current collector 11 may be plate-shaped or thin-film-shaped. In the embodiment, the positive electrode current collector 11 may be omitted.

[0059] The positive electrode active material layer 12 may include a positive electrode active material and a solid electrolyte. Furthermore, the solid electrolyte in the positive electrode layer 10 may be similar to or different from the solid electrolyte in the solid electrolyte layer 40. The solid electrolyte in the positive electrode layer 10 is the same as defined for the solid electrolyte layer 40.

[0060] In the embodiments, the positive electrode active material is capable of reversibly intercalating and deintercalating lithium ions. For example, the positive electrode active material may include at least one of the following: lithium cobalt oxide (hereinafter also referred to as "LCO"), lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide (hereinafter also referred to as "NCA"), lithium nickel cobalt manganese oxide (hereinafter also referred to as "NCM"), lithium manganate, lithium iron phosphate, nickel sulfide, copper sulfide, lithium sulfide, sulfur, iron oxide, or vanadium oxide. For example, the positive electrode active material may include only one of the aforementioned materials or may be a mixture (composite) in which at least two of the aforementioned materials are combined. In one aspect, the use of a combination of positive electrode active materials is mentioned.

[0061] For example, when the positive electrode active material is formed of a lithium salt of a ternary transition metal oxide such as NCA or NCM, and the positive electrode active material includes nickel (Ni), the capacity density of the secondary battery 1 can be increased, and elution of metal from the positive electrode active material in the charged state of the secondary battery 1 can be reduced. Examples of the ternary transition metal oxide may include those represented by the formula LiNi x Co y Al z O2(NCA) or LiNi x Co y Mn z O2(NCM) (where 0<x<1, 0<y<1, 0<z<1, and x+y+z=1). Therefore, the secondary battery 1 can have improved long-term reliability and improved cycle characteristics.

[0062] In the embodiments, the positive electrode active material may be, for example, in the form of particles, and have a shape such as a spherical shape or an ellipsoidal shape. In addition, the diameter of the particles of the positive electrode active material is not particularly limited. Moreover, the amount of the positive electrode active material in the positive electrode layer 10 is not particularly limited.

[0063] In the embodiments, the negative electrode layer 20 may include a negative electrode current collector 21 and a metal layer 22. In the embodiments, the negative electrode current collector 21 may include a material that does not react with lithium, that is, does not form an alloy or compound with lithium. For example, the negative electrode current collector 21 may include at least one of the following: copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), or nickel (Ni). In the embodiments, the negative electrode current collector 21 may include one of the aforementioned elements or an alloy containing at least two of the aforementioned elements. In the embodiments, the negative electrode current collector 21 may be a plate type or a thin film type.

[0064] In an embodiment, the metal layer 22 may include lithium or a lithium alloy. That is, the metal layer 22 may act as a lithium reservoir. Examples of the lithium alloy may include at least one of the following: Li-Al alloy, Li-Sn alloy, Li-In alloy, Li-Ag alloy, Li-Au alloy, Li-Zn alloy, Li-Ge alloy, Li-Si alloy, or Li-C alloy. For example, the metal layer 22 may include one or more of these lithium alloys or lithium itself.

[0065] Furthermore, the thickness of the metal layer 22 can be, for example, within the following ranges: about 1 μm to about 200 μm, such as about 5 μm to about 190 μm, about 10 μm to about 180 μm, about 20 μm to about 170 μm, about 40 μm to about 160 μm, about 80 μm to about 150 μm, or about 100 μm to about 140 μm. When the thickness of the metal layer 22 is less than 1 μm, the metal layer 22 may not adequately function as a lithium reservoir. When the thickness of the metal layer 22 is greater than 200 μm, the weight and volume of the secondary battery 1 increase, and therefore, the capacity characteristics of the secondary battery 1 may deteriorate. In embodiments, the metal layer 22 may be, for example, a metal foil having a thickness in the range of about 1 μm to about 200 μm.

[0066] In one embodiment, the graphite interlayer 30 may comprise a graphite material that forms an alloy or compound with lithium. In another embodiment, lithium is embedded into the graphite interlayer 30 during the initial charging of the secondary battery 1. That is, the graphite material may form an alloy or compound with lithium ions migrating from the positive electrode layer 10. When the secondary battery 1 is charged beyond the capacity of the graphite interlayer 30, lithium is deposited on the back side of the graphite interlayer 30, for example, between the metal layer 22 and the graphite interlayer 30, and the deposited lithium forms a metal layer 23. The metal layer 23 may comprise lithium (e.g., lithium metal or a lithium metal alloy).

[0067] Furthermore, according to the embodiment, during the discharge of the secondary battery 1, lithium in the graphite interlayer 30 and the metal layer 23 is ionized, and the lithium ions move towards the positive electrode layer 10. Therefore, lithium can be used as a negative electrode active material in the secondary battery 1. Moreover, when the graphite interlayer 30 covers the metal layer 23, the graphite interlayer 30 can act as a protective layer for the metal layer 23 and simultaneously prevent lithium from growing as a dendritic structure during deposition. When the crystallization of the graphite interlayer 30 is insufficient, the graphite interlayer may not adequately function as a protective layer.

[0068] If it shows commercially available rechargeable batteries. Figure 3A As shown, when a graphite interlayer 30 is disposed on a surface of a solid electrolyte layer 40 having a shape different from a planar shape, the graphite interlayer 30 and the metal layer 22 can be transformed into LiC6, as shown. Figure 3B and 3CAs shown in the diagram. In this commercially available secondary battery, lithium generated during the charging process can precipitate as dendrites, which can lead to short circuits and reduced capacity in the commercially available secondary battery.

[0069] In one embodiment, the graphite interlayer 30 may include a graphite material having a predetermined crystallinity (crystallinity). For example, such as... Figure 4 As shown, the graphite material in the graphite intermediate layer 30 may have a density of approximately 1000 angstroms. Or larger, for example, about 1000 angstroms - Approximately 1500 Egyptian pounds The crystallite size (La) of the graphite material was measured by X-ray diffraction from the (110) diffraction peak, approximately 500 angstroms. Or larger, for example, about 500 angstroms - Approximately 800 Egyptian The hexagonal interplanar spacing (Lc) in the c-axis direction and the aspect ratio in the range of about 0.44 to about 0.55 were measured by X-ray diffraction from the (002) diffraction peak.

[0070] In an embodiment, the size of the graphite material particles, measured using X-ray diffraction, can be defined as the crystallite size. The method for measuring the crystallite size utilizes... Figure 4 The X-ray diffraction data shown exhibits broadened peaks in the (110) diffraction pattern, and therefore this method allows for estimation of crystallite size and quantitative calculation of crystallite size using the Scherrer equation. In an embodiment, the crystallite size (La) of the graphite material is 1000 angstroms. Or, when larger, the microcrystals may have a size sufficient for crystallization.

[0071] Furthermore, the hexagonal interplanar spacing (Lc) is an indicator of the degree of graphitization of graphite particles. In an embodiment, the hexagonal interplanar spacing (Lc) can be calculated using the Bragg equation by utilizing the peak positions of the (002) diffraction pattern obtained through integration of X-ray diffraction data. In an embodiment, the smaller the hexagonal interplanar spacing (Lc), the more crystals of the graphite particles can be observed. That is, the degree of graphitization can be increased. In an embodiment, the hexagonal interplanar spacing (Lc) of the graphite material can be 500 angstroms. Or larger.

[0072] As described above, when the crystallite size (La) of the graphite material in the graphite interlayer 30 is 1000 angstroms Or larger, and the hexagonal interplanar spacing (Lc) in the c-axis direction, measured by X-ray diffraction from the (002) diffraction peak, is 500 Å. Or, when larger, the graphite intermediate layer 30 is disposed in a planar shape on the surface of the solid electrolyte layer 40, such as... Figure 1 As shown in the figure. On the other hand, when the crystallite size (La) of the graphite material in the graphite intermediate layer 30 is less than 1000 angstroms. Furthermore, the hexagonal interplanar spacing (Lc) along the c-axis, measured by X-ray diffraction from the (002) diffraction peak, is less than 500 Å. At that time, the graphite intermediate layer 30 was not disposed on the surface of the solid electrolyte layer 40 in a planar shape, such as Figure 3A As shown in the image.

[0073] According to embodiments, the average aspect ratio of the graphite material can be in the range of about 0.44 to about 0.55. As used herein, the average aspect ratio of the graphite material represents the ratio (Lc / La) of the hexagonal interplanar spacing (Lc) in the c-axis direction to the crystallite size (La), as measured by X-ray diffraction from the (002) diffraction peak. In embodiments, when the average aspect ratio of the graphite material is within this range, the graphite-based intermediate layer 30 can expand (extend) in a uniform (uniform) direction.

[0074] In an embodiment, the graphite interlayer 30 may further comprise materials other than crystalline graphite. In an embodiment, the graphite interlayer 30 may comprise a mixture of at least one of the following with the graphite material: iron (Fe), zirconium (Zr), gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), or zinc (Zn). However, the embodiment is not limited thereto, and the graphite interlayer 30 may comprise at least one of the following: aluminum (Al), silicon (Si), titanium (Ti), zirconium (Zr), niobium (Nb), germanium (Ge), gallium (Ga), silver (Ag), indium (In), tin (Sn), antimony (Sb), or bismuth (Bi). When the graphite interlayer 30 comprises this mixture, the characteristics of the secondary battery 1 can be improved.

[0075] In embodiments, the graphite intermediate layer 30 may include a binder. For example, the binder may include at least one of the following: polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), or polyvinyl alcohol-polyacrylic acid (PVA-PAA) copolymer, carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR). In embodiments, when the graphite intermediate layer 30 includes a binder, the graphite intermediate layer 30 may be stably disposed on the solid electrolyte layer 40. For example, when the graphite intermediate layer 30 does not include a binder, the graphite intermediate layer 30 may be easily detached from the solid electrolyte layer 40. If a portion of the graphite-based intermediate layer 30 is detached from the solid electrolyte layer 40, the solid electrolyte layer 40 may be exposed to the metal layer 23, and thus a short circuit may occur. In embodiments, when the graphite intermediate layer 30 includes a binder, based on the total weight of the graphite intermediate layer 30, the amount of the binder may be in the range of about 1 weight percent (wt%) to about 10 wt%. When the amount of the binder is less than about 1 wt%, the strength of the layer is insufficient, the properties of the layer may deteriorate, and the layer may become difficult to handle. When the amount of the binder is higher than about 5 wt%, the properties of the secondary battery 1 may deteriorate.

[0076] The thickness of the graphite intermediate layer 30 may be, for example, in the range of about 0.1 μm to about 0.3 μm. When the thickness of the graphite intermediate layer 30 is less than about 0.1 μm, the properties of the secondary battery 1 may not be improved. When the thickness of the graphite intermediate layer 30 is greater than about 0.3 μm, the resistance of the graphite intermediate layer 30 is high, which may deteriorate the properties of the secondary battery 1. When the binder described herein is used, the thickness of the graphite intermediate layer 30 may be suitable for improving the properties of the secondary battery.

[0077] In embodiments, the solid electrolyte layer 40 may be disposed between the positive electrode layer 10 and the negative electrode layer 20. In embodiments, the solid electrolyte layer 40 may include a solid electrolyte material such as Li 3+x La3M2O 12 (where 0≤x≤10), Li3PO4, Li x Ti y (PO4)3 (where 0<x<2 and 0<y<3), Li x Al y Ti z (PO4)3 (where 0<x<2, 0<y<1, and 0<z<3), Li 1+x+y (Al a Ga 1-a ) x (Ti b Ge 1-b ) 2-x Si y P 3-y O 12(where 0≤x≤1, 0≤y≤1, 0≤a≤1, and 0≤b≤1), Li x La y TiO3 (where 0<x<2 and 0<y<3), Li x M y P z S w -(M is Ge, Si, or Sn, where 0<x<4, 0<y<1, 0<z<1, and 0<w<5), Li x N y (where 0<x<4 and 0<y<2), Li x PO y N z (where 0<x<4, 0<y<5, and 0<z<4), SiS2 (Li x Si y S z , where 0<x<3, 0<y<2, and 0<z<4), P2S5 (Li x P y S z , where 0<x<3, 0<y<3, and 0<z<7), Li2O, LiF, LiOH, Li2CO3, LiAlO2, Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2, Li x La y M z O 12 (M is at least one of Te, Nb, or Zr, where 1<x<5, 0<y<4, and 0<z<4), or Li x La y Zr z1 M z2 O 12 (M is at least one of B, Si, Al, Ga, Ge, Te, Nb, Hf, Ta, Ru, W, or Re, where 1<x<5, 0<y<4, 0<z1<4, and 0<z2<4).

[0078] As described herein, the solid electrolyte layer 40 may include an ion-conductive material to allow ion conduction between the positive electrode layer 10 and the negative electrode layer 20, or may include an ion-conductive material and an ion-nonconductive material. Moreover, the solid electrolyte layer 40 may serve as a separation layer that physically or chemically separates the positive electrode layer 10 and the negative electrode layer 20. In an embodiment, the thickness of the solid electrolyte layer 40 may be in the following range: about 10 μm to about 250 μm, for example, about 20 μm to about 225 μm, about 40 μm to about 200 μm, about 60 μm to about 175 μm, about 80 μm to about 150 μm, or about 100 μm to about 125 μm. However, the embodiments are not limited thereto.

[0079] The solid electrolyte layer 40 may further include a binder. Examples of the binder in the solid electrolyte layer 40 may include at least one of the following: styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, or polyethylene. However, the embodiments are not limited thereto, and the binder of the solid electrolyte layer 40 may be the same as or different from the binder of the positive electrode active material layer 12 or the graphite-based intermediate layer 30.

[0080] Figure 6A-6G is a schematic diagram illustrating steps in the method for manufacturing the secondary battery.

[0081] In an embodiment, referring to Figure 6A , the solid electrolyte layer 40 may be formed by using an LLZO-based ceramic (Li x La y Zr z O 12 , where 1<x<5, 0<y<4, and 0<z<4). In an embodiment, starting raw materials (for example, lithium nitrate, lanthanum nitrate, and zirconium oxychloride) are mixed in predetermined amounts to prepare a mixture. The mixture is prepared into a pellet and reacted in vacuum at a predetermined reaction temperature, and the resultant is cooled to prepare the LLZO-based solid electrolyte material. In an embodiment, when a mechanical grinding method is used, the starting raw materials (for example, lithium nitrate, lanthanum nitrate, and zirconium oxychloride) are reacted by stirring using a ball mill, and thus the LLZO-based solid electrolyte material can be prepared. Although the stirring rate and stirring time of this mechanical grinding method are not particularly limited, the production rate of the LLZO-based solid electrolyte material may increase as the stirring rate increases, and the conversion rate from the raw materials to the LLZO-based solid electrolyte material may increase as the stirring time increases.

[0082] In an embodiment, when the mechanical grinding method is used, the starting raw materials may be stirred in isopropanol at a stirring rate of 200 rpm for a stirring time of 10 hours. After completing this stirring process, the resultant may be dried and subjected to a calcination process at a temperature of about 1000°C for 2 hours to 4 hours. A pressure of 50 MPa is applied to the calcined LLZO-based powder to prepare the powder in the form of a pellet, and the pellet is sintered at a temperature of about 1200°C for about 1 hour to about 24 hours, and then cooled to prepare the LLZO-based solid electrolyte material.

[0083] Subsequently, the mixed raw material obtained by the melt cooling method or the mechanical grinding method is heat-treated at a predetermined temperature and pulverized to prepare a solid electrolyte in the form of particles. When the solid electrolyte has glass transition characteristics, the structure of the solid electrolyte may change from amorphous to crystalline through the heat treatment.

[0084] Next, the solid electrolyte obtained therefrom can be deposited using, for example, a suitable layer-forming method such as aerosol deposition, cold spraying (at 20°C), or sputtering to prepare a solid electrolyte layer 40. The solid electrolyte layer 40 can also be prepared by applying pressure to multiple solid electrolyte particles. Alternatively, the solid electrolyte, solvent, and binder can be mixed, coated onto a substrate, dried, and pressed to prepare the solid electrolyte layer 40.

[0085] Then, refer to Figure 6B The two surfaces of the solid electrolyte layer 40 are mechanically polished to produce a clean and flat surface. In one embodiment, the two surfaces of the solid electrolyte layer 40 can be mechanically polished for about 30 seconds to about 2 minutes using sandpaper containing silicon carbide (SiC).

[0086] Next, refer to Figure 6C The solid electrolyte layer 40 can be acid-treated and then dried. In one embodiment, the solid electrolyte layer 40 can be acid-treated in a phosphoric acid solution (H3PO4) for about 5 minutes. In another embodiment, the solid electrolyte layer can be oxidized using an oxidizing gas, and the oxidizing gas can be, for example, oxygen or air, but is not limited thereto. Afterward, the solid electrolyte layer 40 is coated with ethanol and air-dried.

[0087] Subsequently, in the implementation method, refer to Figure 6D A graphite interlayer 30 is coated onto one surface of the solid electrolyte layer 40. In this embodiment, the graphite material in the graphite interlayer 30 may have a density of approximately 1095 angstroms. The crystallite size (La) of the graphite material is approximately 607 angstroms. The hexagonal interplanar spacing (Lc) in the c-axis direction. For example, in an embodiment, the graphite interlayer 30 may be obtained from a graphite material (available from Steadler's HB type). In an embodiment, the graphite interlayer 30 may be coated onto the surface of the solid electrolyte layer 40 using a drawing method or may be disposed on one surface of the solid electrolyte layer 40 using an ink coating method.

[0088] Next, refer to Figure 6EThe stack comprising the negative electrode current collector 21 and the metal layer 22 attached to each other is attached to the graphite interlayer 30. In one embodiment, the metal layer 22 in the form of a metal foil is attached to the negative electrode current collector 21 in the form of a thin film including copper. Here, the metal layer 22 may be a lithium foil or a lithium alloy foil. The stack comprising the negative electrode current collector 21 and the metal layer 22 attached to each other is then attached to the graphite interlayer 30. In one embodiment, the stack comprising the negative electrode current collector 21 and the metal layer 22 attached to each other can be attached to the graphite interlayer 30 by using a cold isostatic pressing process. Here, the pressing process can be performed at a pressure of 250 MPa and a temperature of 20°C for 3 minutes.

[0089] Then, refer to Figure 6F The positive electrode layer 10 is attached to the other surface of the solid electrolyte layer 40. In one embodiment, the material forming the positive electrode active material 12 (positive electrode active material NCM-111 and binder) is impregnated with an ion-based electrolyte solution to prepare the active material. Subsequently, the active material thus obtained is coated onto the positive electrode current collector 11 and dried. Next, the resulting stack is pressed (e.g., by using cold isostatic pressing) to prepare the positive electrode layer 10. The pressing process can be omitted. The mixture of materials constituting the positive electrode active material layer 12 is compressed into a disc or stretched (molded) into a sheet to prepare the positive electrode layer 10. When the positive electrode layer 10 is prepared in this way, the positive electrode current collector 11 can be omitted. The positive electrode layer 10 thus prepared can be attached to the other surface of the solid electrolyte layer 40 by using a pressing process.

[0090] Next, refer to Figure 6G The negative electrode layer 20, graphite intermediate layer 30, solid electrolyte layer 40, and positive electrode layer 10 are sealed in a vacuum through a laminated film 50, thereby completing the manufacture of the secondary battery according to the embodiment. Parts of the positive electrode current collector 11 and the negative electrode current collector 21 can extend from the laminated film 50 without disrupting the vacuum of the battery. The extended portions can be positive electrode layer terminals and negative electrode layer terminals.

[0091] Figure 7 A graph showing the output characteristics of the secondary battery according to the embodiment and the secondary battery prepared in Comparative Example 1. Figure 8 A graph illustrating the charge / discharge characteristics of the secondary battery according to an embodiment. (e.g.) Figure 8 As shown, the areal capacity at cycle 1 and cycle 18 demonstrates that, regardless of the current applied to the battery, the areal capacity at cycle 1 and cycle 18 remains within a narrow range.

[0092] The secondary battery 1 according to the embodiment is charged beyond the charging capacity of the graphite interlayer 30. That is, the graphite interlayer 30 is overcharged. During the initial charging, lithium is inserted into the graphite interlayer 30. When the charging exceeds the capacity of the graphite interlayer 30, lithium is deposited in (or on) the metal layer 22. During discharge, the lithium in the graphite interlayer 30 and the lithium in (or on) the metal layer 22 are ionized and move toward the positive electrode layer 10. Therefore, the secondary battery 1 can use lithium as the negative electrode active material. Moreover, when the graphite interlayer 30 covers the metal layer 22, the graphite interlayer 30 acts as a protective layer for the metal layer 22 and can simultaneously suppress the precipitation and growth of dendrites. Therefore, short circuits and capacity reduction of the secondary battery 1 can be suppressed, and further, the characteristics of the secondary battery 1 can be improved.

[0093] Example

[0094] Example 1

[0095] In Example 1, by performing as in Figure 6A-6G The process mentioned in the article is used to prepare secondary batteries.

[0096] Comparative Example 1

[0097] In Comparative Example 1, the graphite interlayer 30 is a graphite material comprising bare graphite particles. The crystal size (La) and hexagonal interplanar spacing (Lc) of the bare graphite particles were not measured. A secondary battery was prepared for testing in the same manner as in Example 1, except that the graphite interlayer 30 comprising the aforementioned graphite material was used.

[0098] Charge / discharge analysis

[0099] The charge / discharge characteristics of the secondary batteries prepared in Example 1 and Comparative Example 1 were evaluated by the following charge / discharge tests. The charge / discharge tests were performed as follows: the secondary batteries were placed in a constant temperature chamber at 60°C. During the first to sixth cycles, the secondary batteries were charged with 0.5 mA / cm². 2 The battery was charged with a constant current until the voltage reached 4.2V, and then charged with a constant voltage of 4.2V. Then, the battery was charged with 0.5mA / cm². 2 Discharge the battery with a constant current until the battery voltage reaches 2.8V. During cycles 7 through 11, discharge the battery with a constant current of 1.0 mA / cm². 2 The battery was charged with a constant current until the battery voltage reached 4.2V, and then charged with a constant voltage of 4.2V. Then, the battery was charged with 1.0mA / cm². 2 Discharge the battery with a constant current until the battery voltage reaches 2.8V. During cycles 12 through 16, discharge the battery with a constant current of 1.6mA / cm. 2The battery was charged with a constant current until the voltage reached 4.2V, and then charged with a constant voltage of 4.2V. Then, the battery was charged with 1.6mA / cm². 2 Discharge the battery with a constant current until the battery voltage reaches 2.8V. During the 17th and 18th cycles, discharge the battery with a constant current of 2.0mA / cm. 2 Charge with a constant current until the battery voltage reaches 4.2V, and then charge with a constant voltage of 4.2V.

[0100] Reference Figure 7 and 8 The battery of Example 1 was stably charged / discharged until at least the 18th cycle, and it was confirmed that the energy efficiency of the battery of Example 1 was better than that of the battery of Comparative Example 1.

[0101] While many details have been set forth in the foregoing description, they should be interpreted as illustrative of preferred embodiments and not as limiting the scope of the invention. For example, those skilled in the art will recognize that various modifications can be made to the secondary battery described with reference to the accompanying drawings and the method of preparing the secondary battery. In particular, for example, the secondary battery may be an all-solid-state secondary battery or may partially use a liquid electrolyte, and the concept and principles of the embodiments can be applied to batteries other than lithium batteries. For this reason, the scope of the invention should not be limited by the described embodiments, but rather by the technical spirit described in the claims.

[0102] It should be understood that the embodiments described herein are for descriptive purposes only and are not intended to be limiting. Descriptions of features, aspects, or advantages within each embodiment should be considered applicable to other similar features, aspects, or advantages in other embodiments. Although one or more embodiments have been described with reference to the accompanying drawings, those skilled in the art will understand that various changes in form and detail may be made therein without departing from the spirit and scope defined by the appended claims.

Claims

1. Secondary batteries, including: The positive electrode layer includes the positive electrode active material layer; The negative electrode layer includes a negative electrode current collector and a metal layer disposed on the negative electrode current collector; A solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer; as well as A graphite interlayer coated on the surface of the solid electrolyte layer and disposed between the solid electrolyte layer and the negative electrode layer. The graphite interlayer comprises a graphite material, and the crystallites of the graphite material have a crystallite size of 1000-1500 angstroms as measured by the (110) diffraction peak during X-ray diffraction analysis. Furthermore, it has a hexagonal interplanar spacing of 500-800 Å in the c-axis direction as measured by the (002) diffraction peak during X-ray diffraction analysis, and an aspect ratio in the range of 0.44-0.55, wherein the aspect ratio represents the ratio of the hexagonal interplanar spacing in the c-axis direction of the graphite material in the graphite interlayer to the crystallite size, as measured by the (002) diffraction peak during X-ray diffraction. The thickness of the graphite interlayer is in the range of 0.1 micrometers to 0.3 micrometers. The metal layer comprises at least one of lithium or a lithium alloy.

2. The secondary battery of claim 1, wherein the graphite intermediate layer further comprises at least one of the following: iron, zirconium, gold, platinum, palladium, silicon, silver, aluminum, bismuth, tin, or zinc.

3. The secondary battery according to claim 1, wherein the positive electrode active material layer comprises at least one of the following: lithium cobalt oxide, lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium manganese oxide, or lithium iron phosphate.

4. The secondary battery according to claim 1, wherein the positive electrode active material layer comprises at least one of the following: LiNi x Co y Al z O2 or LiNi x Co y Mn z O2, wherein 0<x<1, 0<y<1, 0<z<1, and x+y+z=1.

5. The secondary battery according to claim 1, wherein the solid electrolyte layer comprises at least one of the following: Li3PO4; Li x Ti y (PO4)3, where 0<x<2 and 0<y<3; Li x Al y Ti z (PO4)3, where 0<x<2, 0<y<1, and 0<z<3; Li 1+x+y (Al a Ga 1-a ) x (Ti b Ge 1-b ) 2-x Si y P 3-y O 12 , where 0≤x≤1, 0≤y≤1, 0≤a≤1, and 0≤b≤1; Li x La y TiO3, where 0<x<2 and 0<y<3; Li x M y P z S w , where M is at least one of Ge, Si, or Sn, and 0<x<4, 0<y<1, 0<z<1, and 0<w<5; Li x N y , where 0<x<4 and 0<y<2; Li x PO y N z , where 0<x<4, 0<y<5, and 0<z<4; Li x Si y S z , where 0<x<3, 0<y<2, and 0<z<4; Li x P y S z , where 0<x<3, 0<y<3, and 0<z<7; Li2O; LiF; LiOH; Li2CO3; LiAlO2; Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2; or Li x La y M z O 12 , where M is at least one of Te, Nb, or Zr, and 1<x<5, 0<y<4, and 0<z<4.

6. The secondary battery of claim 1, wherein the thickness of the solid electrolyte layer is in the range of 10 micrometers to 250 micrometers.

7. The secondary battery of claim 1, wherein the graphite intermediate layer further comprises a binder.

8. The secondary battery of claim 7, wherein the binder comprises at least one of the following: polyvinylidene fluoride, polyvinyl alcohol, or polyvinyl alcohol-polyacrylic acid copolymer, carboxymethyl cellulose, styrene-butadiene rubber, and the amount of the binder is in the range of 1% to 10% by weight based on the total weight of the graphite interlayer.

9. The secondary battery according to claim 1, wherein the lithium alloy comprises at least one of the following: Li-Al alloy, Li-Sn alloy, Li-In alloy, Li-Ag alloy, Li-Au alloy, Li-Zn alloy, Li-Ge alloy, or Li-Si alloy.

10. The secondary battery as claimed in claim 1, wherein the secondary battery is a lithium battery.

11. The secondary battery of claim 1, wherein the positive electrode layer further comprises a positive electrode current collector disposed on the surface of the positive electrode active material layer.

12. A method for preparing a secondary battery according to any one of claims 1-11, the method comprising: Provide a solid electrolyte layer; The surface of the solid electrolyte layer is mechanically ground to provide a ground surface; The solid electrolyte layer is brought into contact with an oxidizing gas to provide an oxidized solid electrolyte layer; The oxidized solid electrolyte layer is dried in air to provide a dried solid electrolyte layer; A graphite intermediate layer is coated on the polished surface of the solid electrolyte layer to provide a coated solid electrolyte layer; A stack comprising a metal layer and a negative electrode current collector is disposed on the coated solid electrolyte layer to form a negative electrode layer; and A positive electrode layer, including a layer of positive electrode active material, is disposed on the surface opposite to the negative electrode layer of the dried solid electrolyte layer to form a secondary battery.

13. The method of claim 12, wherein the coating of the graphite intermediate layer is provided by ink application or pencil drawing.

14. The method of claim 12, wherein disposing the stack comprising the metal layer and the negative electrode current collector on the coated solid electrolyte layer further comprises cold isostatic pressing to dispose the stack comprising the metal layer and the negative electrode current collector on the coated solid electrolyte layer.

Citation Information

Patent Citations

  • Graphite material for use in negative electrode of lithium-ion secondary battery and process for producing the same

    CN1198598A

  • Lithium metal electrode for lithium secondary battery with safe protective layer and lithium secondary battery comprising the same

    KR1020160052351A

  • Negative electrode for lithium secondary battery, method for preparing the same and lithium secondary battery comprising the same

    KR1020190033922A